2012
DOI: 10.1099/jmm.0.041699-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Candida albicans yeast–hyphal transition and biofilm formation by Solidago virgaurea water extracts

Abstract: Xerostomia is a decrease of saliva secretion, which can unbalance the oral microflora, mainly to the benefit of Candida albicans. The aim of the present study was to find a plant extract that could create an unfavourable environment for Candida, and would, therefore, be appropriate for use in a dry-mouth daily-care mouthwash. Water extract from the herbaceous plant Solidago virgaurea (Goldenrod) was selected due to its saponin content (plant detergents). Saponin concentrations reached 0.7 and 0.95 mg ml "1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
0
39
0
1
Order By: Relevance
“…Meanwhile, the availability of well-established pharmaceutics is greatly reduced due to the rapidly growing number of multidrugresistant strains. The current paradigm in the discovery of novel promising antimicrobial therapeutics postulates their targeting to microbial virulence factors/abilities rather than direct biocidal activity (Bink et al, 2011;Chevalier et al, 2012;Gauwerky et al, 2009;Naicker & Patel, 2013;Rajeshkumar & Sundararaman, 2012). The antifungal potential of tested SFs from plant extracts seems to fulfil these needs.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the availability of well-established pharmaceutics is greatly reduced due to the rapidly growing number of multidrugresistant strains. The current paradigm in the discovery of novel promising antimicrobial therapeutics postulates their targeting to microbial virulence factors/abilities rather than direct biocidal activity (Bink et al, 2011;Chevalier et al, 2012;Gauwerky et al, 2009;Naicker & Patel, 2013;Rajeshkumar & Sundararaman, 2012). The antifungal potential of tested SFs from plant extracts seems to fulfil these needs.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that some plant extracts efficiently inhibit the biofilm formation of C. albicans [24]. Moreover, EOs especially with known antibacterial effects have the potential to be used in food industry as preservatives and to increase the shelf life of products.…”
Section: Introductionmentioning
confidence: 99%
“…However, this working dose was previously described to contain around 0·25 mg ml −1 of saponin‐like products (Chevalier et al . ). We excluded a possible saponin‐mediated detergent action by showing first that the growth of planktonic forms of the C. albicans 10231 strain and of the three different clinical isolates was not affected by the SV extract (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…We previously discovered that the crude water extract from SV was very efficient to prevent formation of Candida biofilms and that it was also capable to eradicate preformed biofilms (Chevalier et al . ). This study thus revealed the potential value of this plant extract as a new candidate against oral Candida infection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation